Development of Digital History Learning Media: Photobooks and Historical Collections on Agriculture and Colonial Plantations to Enhance Student Understanding - Hilmiah, Anis Syatul; Umamah, Nurul; Hartono, Fernanda Prasky; Zulfikar, Fachri (LPPM Universitas Pendidikan Mandalika, 2025)
This research aims to develop innovative media, specifically a history digital collection and photobook, focusing on agricultural intensification and colonial plantations in ex-Karesidenan Besuki. The goal is to enhance student engagement and understanding through a Research and Development (R&D) approach using the ADDIE model. The digital product developed contains a collection of photos, documents, and visual narratives to enrich history learning at the high school level. Data analysis involves processing historical data to identify patterns, such as economic impacts, social changes, or environmental effects. A mixed-methods approach is employed, combining quantitative and qualitative analysis to balance numerical evidence with contextual storytelling from the archives. The study successfully developed a history learning media in the form of a History Digital Collection and Photobook. The results showed that this media was effective in increasing student engagement and understanding, with the experimental class achieving an average post-test score of 82.72, exceeding the set KKM. In contrast, the control class scored 72.05. The t-test analysis confirmed the effectiveness of this media, with strong significance (t count = 6.78; t table = 1.69). Thus, the History Digital Collection and Photobook serve not only as learning tools but also as a means of preserving local history, strengthening the community's identity and historical awareness.